Synthesis, molecular modeling and harnessing the antimicrobial activity of new pyrazine-thiadiazole hybrids - Hana M. Abumelha; Nuha M. Halawani; Abdulrahman S. Alharbi; Rabah N. Alsulami; Jihan Qurban; Khadra B. Alomari; Ameena M. Al-Bonayan; Nashwa El-Metwaly (BMC Chemistry)
Abstract Various pyrazine-substituted thiadiazole hybrid compounds 5a-c, 9a-c, and 11a-c have been synthesized and elucidated using spectral measurements. Despite the alternative spatial structures, the DFT modeling of the targeting hybrids revealed comparable HOMO–LUMO configurations and energies, which were employed in the estimation of some chemical reactivity parameters. Further, the antimicrobial efficacy of these hybrids was measured against bacterial and fungal strains. Hybrids 5b, 5c, and 9c demonstrated effective antimicrobial activities, comparable to reference drugs. Hybrid 5b exhibited broad-spectrum activity, while 9c showed the strongest antifungal effectiveness. Moreover, in vitro assessment of dihydrofolate reductase (DHFR) enzyme inhibition revealed notable activity; hybrid 9c demonstrated the highest potency (IC50 = 0.05 ± 0.63 µM), surpassing methotrexate (IC50 = 1.23 ± 0.51 µM). The molecular docking study of synthesized hybrids revealed significant bindings with key amino acid residues of the target 1DLS receptor; compounds 5c and 9b exhibited the strongest bindings (S = − 15.0667 and − 16.1657 kcal/mol, respectively). Furthermore, ADMET evaluation of the synthesized compounds afforded noteworthy pharmacokinetic characteristics and drug-likeness attributes. Hybrid 11a emerged as the most promising candidate, owing to its highest bioavailability and BBB permeability, warranting further investigation. These findings establish a basis for prioritizing hybrids with advantageous ADMET profiles in future drug development efforts.